2020
DOI: 10.4236/oalib.1106094
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Undergraduate Students’ Attitude and Perception towards the Use of Electronic Information Resources (EIRs) among Undergraduate Students in Selected Universities in Eastern Cape, South Africa

Abstract: This study sought to investigate the attitudinal behavior and perceptions of undergraduate students in University of Fort Hare and Rhodes, towards their utilization of e-information resources (EIRs). The essence was to ascertain whether their attitude and perception have a positive or negative impact on e-resource use in selected universities in Eastern Cape, South Africa. The purposive and proportionate stratified random sampling techniques were employed in selecting the study population and sample size while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Thus, it can be concluded that students (Post-Graduate and Ph.D. level) of agriculture universities had a positive and favourable attitude towards e-resources but require proper exposure and training at the right time for the better utilization of all e-resources. The present findings are in line with the findings of Kumbar [13], Radjagopal and Chinnasamy [14], Novamaka [15], Sepahpanah et al [16], Oresanya and Oresanya [6], Viswanathan and Sasireka [17], Kumar and Anjaiah [18], Anhwere [19], Mishra [8] and Olatoye et al [20] who indicated that majority of the scholars agreed that Electronic information sources provide predecessors different opportunities for career development and -resources make life easier and comfortable by e-shopping, e-ticket, ebanking etc. Whereas, Borthakur and Chandra [21] reported that majority of respondents (90%) viewed viruses, hackers, and pornographic websites as the three biggest drawbacks of using the internet, followed by misuse (80%), harm to Indian culture (70%), time wastage (60%) and contribution to the web world (50%).…”
Section: ) Statement Wise Attitude Of Students (Post-graduate and Phd...supporting
confidence: 93%
“…Thus, it can be concluded that students (Post-Graduate and Ph.D. level) of agriculture universities had a positive and favourable attitude towards e-resources but require proper exposure and training at the right time for the better utilization of all e-resources. The present findings are in line with the findings of Kumbar [13], Radjagopal and Chinnasamy [14], Novamaka [15], Sepahpanah et al [16], Oresanya and Oresanya [6], Viswanathan and Sasireka [17], Kumar and Anjaiah [18], Anhwere [19], Mishra [8] and Olatoye et al [20] who indicated that majority of the scholars agreed that Electronic information sources provide predecessors different opportunities for career development and -resources make life easier and comfortable by e-shopping, e-ticket, ebanking etc. Whereas, Borthakur and Chandra [21] reported that majority of respondents (90%) viewed viruses, hackers, and pornographic websites as the three biggest drawbacks of using the internet, followed by misuse (80%), harm to Indian culture (70%), time wastage (60%) and contribution to the web world (50%).…”
Section: ) Statement Wise Attitude Of Students (Post-graduate and Phd...supporting
confidence: 93%
“…According to Quadri et al (2014), undergraduates use EIRs to retrieve accurate, adequate, relevant and up-to-date information for class assignments, seminars, writing term papers and projects. Olatoye et al (2020) attributed the patronage of EIRs by undergraduates to the fact that e-information resources are time-saving and have the capacity to provide users with advanced functionality features beyond what is achievable in printed format. Similarly, Andreou (as cited in Omeluzor et al , 2016) also describes some of the advantages of using EIRs to include: quick search, ability to make complicated searches using a combination of keywords, enables simultaneous searching and saving of multiple files by users, possibility of being printed and can be updated more often than printed tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, literature have indicated that the undergraduates use EIRs and services much more than any other category of students in the university (Olatoye et al , 2020). Consequently, it can be presumed that they are more prone to plagiarism, violation of copyright laws and other unethical issues.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation